CONTRIBUIÇÃO DOS VAZAMENTOS NA REDE DE DISTRIBUIÇÃO DE ÁGUA PARA A RECARGA DE AQUÍFERO LIVRE - LARISSA ALVES FERNANDES XAVIER (2024)
Although there are studies that show that groundwater recharge values can be minimized in urban environments due to reduced infiltration, there is also research that points to the possibility of recharge occurring from infiltration and percolation of water from leaks in public supply pipes. In this context, considering the importance of recharge for the continued use of groundwater in different uses and the necessity of identifying events that affect its quantity and quality, this work investigated whether leaks in supply system pipes recharge a free aquifer in an urban environment. To this end, an experiment was installed responsible for transmitting water to the soil in an induced (artificial) manner and, consequently, to the free aquifer. In addition, the volume leaked, the water level in piezometers and the water temperature were monitored. With the data series of leaked volume, precipitation and water levels, we calculated the recharge in each piezometer; we compare the recharge series using statistical tests; and we check the correlation between precipitation and water levels. The results show that the volume leaked experimentally was not able to change the local recharge and heating water as a tracer is not recommended for use in studies with low volumes. Recharge in the study area was, on average, 110 mm (considering the studied period of 213 days) and corresponds to 8% of total local precipitation.